Soybean seed growth dynamics exposed to heat and water stress during the filling period under field conditions - Veas, Rodolfo Ezequiel (2021)
Soybean production can be affected by heat (HS) and water stress (WS). However, studies on effects of stresses combination under field conditions are still scarce. The objective of this study was to evaluate the impact of HS, WS and their interaction (HS × WS) during seed filling on seed weight, seed growth rate (SGR) and seed filling duration (SFD) of same phenological age pods from different canopy positions. Two soybean genotypes were exposed to four treatments during seed filling: control (irrigated plots at ambient temperature), HS (plots under temperatures >32°C for 6 hr/day during 15 days), WS (plots under 25% of soil water content, during entire seed filling) and HS × WS. Stresses interaction caused similar responses to WS alone, decreasing yield and its components (seed number and weight), as well as seed weight for each canopy position (SWCP), SGR and SFD. Non-significant effect of irrigated HS and non-additive effects was observed in HS × WS plots, exhibiting WS a dominant effect over HS. The SWCP strongly correlated with SGR, exhibiting upper position a trend to higher SWCP than lower one. Seed maximum water content and pod weight, positively associated with SWCP, indicated seed metabolic limitations under WS and HS × WS. Our results advance in the understanding of SW determination under abiotic stresses and highlight the importance of identifying pods of same phenological age to establish accurate comparisons between seeds from different canopy positions.